KETAHANAN KELUARGA DI PESANTREN HIDAYATULLAH BALIKPAPAN - Paryadi, Paryadi; Sadari, Sadari (Asosiasi Dosen PTKIS Indonesia, 2022)
The family divorce rate in Indonesia is high and worrying because it is increasing every year. This is because of the various problems and challenges in each family member in Indonesia. Despite various government efforts to strengthen the resilience of this family institution. On the one hand, Pesantren Hidayatullah Balikpapan with its vision and mission, the program is able to construct family resilience based on the pesantren community. So that the divorce rate is low and there are minimal family problems. The results of the research on family resilience built by the Hidayatullah Islamic Boarding School in Balikpapan with various efforts and programs in accordance with the maqashid shari'ah, namely the protection of ushul khamsah (religion, soul, mind, lineage and property). In terms of aspects and indicators of family resilience set by the ministry of Empowerment, Protection of Women and Children, there is also strong relevance.